OnabotulinumtoxinA: An Effective Tool in the Therapeutic Arsenal for Chronic Migraine With Medication Overuse - Caronna, Edoardo; Gallardo, Victor José; Hernández-Beltrán, Natalia; Torres-Ferrus, Marta; Pozo-Rosich, Patricia (Frontiers in Neurology, 2018)
Objective: To evaluate the early response of onabotulinumtoxinA as a treatment tool in patients with chronic migraine (CM) and medication overuse (MO). Patients & Methods: This is a retrospective study in patients with CM and MO who received two cycles of onabotulinumtoxinA infiltrations following PREEMPT protocol. We evaluated the efficacy of onabotulinumtoxinA in MO resolution, defined as less than 10 days/month of acute medication intake (triptans, opioids and combinations) or 15 days/month (non-steroidal anti-inflammatory drugs - and simple analgesics). In addition, we analyzed changes in headache frequency, pain intensity, and headache-related disability (MIDAS scale). A multivariate analysis was carried out to identify factors independently related to MO resolution. Results: We included 139 consecutive patients with CM and MO. After 2 cycles of onabotulinumtoxinA, 73.4% had 50% reduction in acute medication intake and 57.6% achieved MO resolution. 7.9% of patients did not use any acute medication after treatment. Even though both MO-ongoing group and MO-resolution group improve in headache frequency, the reduction was significantly higher for the group which discontinued the use of acute medication after onabotulinumtoxinA treatment (p<0.001). In this group, 73.0% reduced headache frequency 50%. Daily headache changed from 71.2% to 23.2% (p<0.001). Both groups showed an improvement in pain intensity and in MIDAS score (p<0.05). In the multivariate analysis we observed that MO resolution had an inverse association with medication intake at baseline (OR:0.294, p<0.05) and a direct association with frequency (OR:20.455, p<0.001) and MIDAS score (OR: 6.465, p<0.05) improvements. Conclusion: OnabotulinumtoxinA has an early beneficial effect in a substantial proportion of patients on the discontinuation of acute medication in patients with CM and MO. Therefore, onabotulinumtoxinA might be considered a therapeutic tool in CM with MO.